A tutorial about diagnostic methodology with dementia data. (29th July 2009) - Shanmugam, Ramalingam
The purpose of the diagnostic methodology is to discuss, estimate and interpret medical parameters such as sensitivity, specificity and prevalence of a diseased population in the chosen community for the research study. However, this statistical methodology is not fully and correctly comprehended by all in the medical professions although everyone admits to its high importance and use. This article is therefore carefully prepared to alleviate commonly experienced conceptual confusions. To ease the comprehension of difficult material, real-life data of 135 participants with dementia illness are considered, analysed and interpreted. Consequently, even less technically oriented medical professionals can learn how to interpret the results from the diagnostic methodology. Critical comments with discussions in the end help to appreciate the operational procedure of the diagnostic methodology.